EFL secondary school students' experiences in performing ideas using Prezi presentation - Nur Jamilah; Mutmainnah Mustofa; Sugeng Hariyanto; Fatimatus Zahroh (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2022)
Using sophisticated technology in EFL has been a source of considerable debate. As a part of the Web 2.0 movement, Prezi lets users generate, produce, and preserve virtual demonstrations. While a substantial study has been conducted on the benefits and downsides of utilizing Prezi presentations, there is scarce research on students' experiences with using Prezi. The study aims to look at pupils' perspectives on using Prezi in learning English to fill the gap. Twenty students from a private secondary school in Mojokerto, Indonesia, were examined. This exploratory qualitative case study used a purposive sampling strategy. They answered ten interview questions, which the researchers examined using content analysis. The findings revealed that students' experiences using Prezi and making Prezi demonstrations could be divided into four primary topics: serviceability, effectiveness, design, and hindrances. Using Prezi, students experienced producing more interactive visuals for their production than standard PowerPoint slides. In line with this study, Prezi's revolutionary features transform the report from a monotonous and direct way into a fascinating, stunning, practical, and nonlinear style. The findings of this study, in practice, demand the implementation of academic tutorials for classroom teachers to construct their core principles of teaching utilizing the Prezi presentation.